Morphological and mitochondrial DNA characteristics of two cultured species of cupped-oysters (Bivalvia : Ostreidae) in Hong Kong : towards a significant taxonomic name change - Lam, Katherine; Morton, Brian; Boudry, Pierre; Heurtebise, Serge (Proceedings of an Internation Workshop, Reunion conference, Hong Kong 21626 October 2001, 2003)
Cultured cupped-oysters species in Hong Kong have rarely been differentiated properly due to similarities in shell characters. This study attempted to characterize putative Crassostrea gigas and Crassostrea ariakensis by morphological and genetic means. Allometric ratios of shell height/length and depth/length were significantly different between the two species. Restriction fragment length polymorphism (RFLP) of a PCR amplified mitochondrial COI (cytochrome oxidase I) fragment was used to examine genetic differentiation between putative C. gigas from Hong Kong and previously studied populations of Crassostrea from Europe, Japan and Taiwan. The two Hong Kong species are not only morphologically, but also genetically different from each other in terms of ail the four restriction sites tested (TaqI, Sau3A, HhaI and MseI) showing that RFLP in this COI fragment is a useful tool to distinguish them. Putative Crassostrea gigas oysters in Hong Kong present a new and unique monomorphic COI haplotype when compared with C.gigas and C. angulata from Europe and Asia. The numbers of nucleotide differences between this Hong Kong Crassostrea species and C. gigas/C. angulata populations were high (-13-15) and significantly different (ail p-values of pairwise test < 0.01). These results, therefore, suggest that the Hong Kong individuals represent a new species of cupped-oyster and this is currently being described